(untitled) (Journal of Organizational Psychology, 2021)
Teacher stress and burnout under non-crisis situations are well-documented challenges. However, during COVID-19, teachers have faced new and unexpected stressors, potentially contributing to rising burnout and attrition. Yet many teachers have also demonstrated great resilience and found effective ways to manage their well-being. To explore teacher well-being during COVID-19, this study used a longitudinal qualitative design that employed recurrent cross-sectional analysis using wo conceptual frameworks including the job-demands-resource model of well-being and the hierarchy of needs theory of motivation. Researchers investigated 25 teacher’s well-being during COVID-19 at two time points (June 2020 and March 2021). Both barriers and facilitators of well-being at the individual and contextual levels are discussed.